Avaliação do efeito da solução de hipoclorito de sódio 5,25% aquecida sobre a rugosidade dentinária - Côgo, Thayany Giori (2014)
The aim of this study was to evaluate the effect of the heated solution of sodium hypochlorite (NaOCl) 5.25% on the roughness of human dentin. It was selected five healthy extracted third molar teeth which were obtained a coronary dentin disc with 3 millimeters (mm) thick from each tooth. Aiming to use an experimental single-tooth model (unique sample), two longitudinal cuts were made on each disk generating four fragments, three of which were randomly selected for application of NaOCl 5.25% solution at different temperatures forming three experimental groups: GINaOCl 5.25% at 25 °C (ambient temperature); GII- NaOCl 5.25% at 37 °C; GIIINaOCl 5.25% at 45 °C. The dentinary surface roughness (Ra and Sa) was measured using a three-dimensional surface topography before and after the application of the solution of sodium hypochlorite 5.25% for 20 minutes in different thermic treatments. The obtained data were statistically analyzed using the Wilcoxon Mann-Whitney and Kruskal Wallis tests with significance level of 5%. The analyzes were performed in the single-tooth model (Ra) and grouped samples according to thermic treatments (Ra e Sa). There was no statistically significant difference between the dentinary roughness (initial and final), both to Ra as to Sa after the application of NaOCl 5.25%, independent of temperature used. The results did not differ when the samples were evaluated through single-tooth model or grouped samples. It was concluded that heating NaOCl 5.25% solution did not cause increase in the dentinary roughness (Ra) on a same tooth and in grouped samples (Ra and Sa).